2007
DOI: 10.1002/ps.1476
|View full text |Cite
|
Sign up to set email alerts
|

Preference of birds for zinc phosphide bait formulations

Abstract: The bait formulations tested may not considerably enhance the safety of birds when using zinc phosphide for rodent control. Field testing other combinations of bait colour and shape to minimise background contrast may result in bait with higher potential for bird protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…If lethal dose application rates are indeed higher, the consequences of secondary poisoning for nontarget species will need to be assessed. While it is possible for nontarget deaths, 32 , 33 in the Australian context very few have been recorded provided label conditions are adhered to when undertaking baiting. 3 , 8 Tkadlec and Rychnovský 33 found that for ZnP‐poisoned common voles ( Mictrotus arvalis ), 99% of ZnP residues remained in their gastrointestinal tracts.…”
Section: Discussionmentioning
confidence: 99%
“…If lethal dose application rates are indeed higher, the consequences of secondary poisoning for nontarget species will need to be assessed. While it is possible for nontarget deaths, 32 , 33 in the Australian context very few have been recorded provided label conditions are adhered to when undertaking baiting. 3 , 8 Tkadlec and Rychnovský 33 found that for ZnP‐poisoned common voles ( Mictrotus arvalis ), 99% of ZnP residues remained in their gastrointestinal tracts.…”
Section: Discussionmentioning
confidence: 99%
“…However, in spite of some variation between populations in the speed of bait carrier removal between enclosures, lentil‐shaped pellets were also heavily depleted after 12 h, which indicates high attractiveness of such pellets for common voles at the high population density considered in the enclosure trial. If the palatability of lentil‐shaped pellets was similar in the field, their application may offer some protection to birds from accidental poisoning, as pelleted bait might be less attractive to birds than wheat kernels 21. Furthermore, in contrast to wheat, where zinc phosphide is concentrated on the surface, there is a homogeneous mixture of active ingredient and bait base in pelleted bait.…”
Section: Discussionmentioning
confidence: 99%
“…Water was available ad libitum at all times in a trough in the centre of each aviary. Food was offered in plastic food racks in each corner of the aviary (details in Jacob and Leukers). During a 1 week acclimatisation period, pigeons received 100 g of a bird food mix of 40% Milo ( Sorghum bicolor ), 25% wheat ( Triticum aestivum ), 20% peas ( Pisum sativum ), 5% buckwheat ( Fagopyrum sagittatum ), 5% vetch ( Vicia spp.)…”
Section: Methodsmentioning
confidence: 99%